Enabling the business environment for healthy and sustainable food: IFPRI-GAIN/SBN roundtable event - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Food supply systems have changed dramatically over the past half century, with enormous advancements in improving food distribution systems, food processing technologies, and delivery of food services. On November 28, 2018, representatives from private sector companies, government ministries, and research organizations gathered in Bangkok, Thailand to discuss the challenges and opportunities presented by these changes. The roundtable event focused on a series of overarching questions: What can be done to increase efficiency in agricultural markets; what innovations are needed to make these markets more inclusive; and what is needed to ensure they are more sustainable and healthier? Several major themes emerged during the discussion that will be important to focus on as the FIPP program develops.